Wrap around field plate technique for GaN Schottky barrier diodes. Issue 1736 (19th December 2014) - Kolli, Sowmya; Hickman, Robert; Alphenaar, Bruce W
Abstract: In this paper, we propose a wrap around field termination technique for a vertical Schottky barrier diode fabricated on a free standing GaN substrate. Unlike conventional field plate designs, in the wrap around structure the field plate surrounds the active device area. This allows for better control of the electric field distribution, and reduces field-crowding. 2D finite element simulations using ATLAS show a uniform field distribution across the device. Calculations show that the Ron increases relative to the conventional field plate. A break down voltage of 1300V was predicted for a 5um thick epilayer.